2021
DOI: 10.1038/s41598-021-88938-6
|View full text |Cite
|
Sign up to set email alerts
|

Persistent deterioration of visuospatial performance in spaceflight

Abstract: Although human adaptation to spaceflight has been studied for decades, little is known about its long-term effects on brain and behavior. The present study investigated visuospatial performance and associated electrophysiological responses in astronauts before, during, and after an approximately half-year long mission to the International Space Station. Here we report findings demonstrating that cognitive performance can suffer marked decrements during spaceflight. Astronauts were slower and more error-prone o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 55 publications
0
19
1
Order By: Relevance
“…In this task, subjects are either instructed to compare or align the orientation of the actual line(s) with the earlier presented one. Takács et al (2021) found significantly poorer performance in 5 astronauts during both the earlier (∼1.5 weeks) and later (∼1.5–2 months) stages of a half-year-long flight and even 2–8 days after return. ERP indicators showed changes similar to the behavioral data (reduced P3a and P3b amplitude), with the difference that while behavioral measures did return to pre-flight levels 2–3 weeks after landing, the ERP amplitudes did not.…”
Section: Cognitive Results Of Space and Head-down Tilt Bedrest Studie...mentioning
confidence: 83%
See 2 more Smart Citations
“…In this task, subjects are either instructed to compare or align the orientation of the actual line(s) with the earlier presented one. Takács et al (2021) found significantly poorer performance in 5 astronauts during both the earlier (∼1.5 weeks) and later (∼1.5–2 months) stages of a half-year-long flight and even 2–8 days after return. ERP indicators showed changes similar to the behavioral data (reduced P3a and P3b amplitude), with the difference that while behavioral measures did return to pre-flight levels 2–3 weeks after landing, the ERP amplitudes did not.…”
Section: Cognitive Results Of Space and Head-down Tilt Bedrest Studie...mentioning
confidence: 83%
“…The effect of spaceflight and HDBR on spatial working memory was tested with the following tasks: the Line orientation memory task, the Array match to sample and Grid match to sample tasks, the Spatial location task. Regarding space, performance in the Line orientation memory task was investigated in a case study of a 6-day-long space mission ( Benke et al, 1993a ; Benke et al, 1993b ) and in 2 half-year-long space missions ( McIntyre et al, 2001 ; Takács et al, 2021 ). In this task, subjects are either instructed to compare or align the orientation of the actual line(s) with the earlier presented one.…”
Section: Cognitive Results Of Space and Head-down Tilt Bedrest Studie...mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous findings have reported significant slower and more error visuospatial performance on-orbit than on Earth which was accompanied by event-related brain potentials modifications reflecting diminished attentional resources 35 . Our present results could not provide a demonstration of significant deterioration of the performance of the virtual docking.…”
Section: Discussionmentioning
confidence: 87%
“…The "NEUROSPAT" project has demonstrated the potential of this technology on the ISS (Figure 1). It has confirmed changes in visuo-attentional activity, visuospatial performance, brain activity, and effects of space travel on sleep quantity [28][29][30][31]. EEG has also been used in space to measure changes in neurocognitive performance and brain activity that result from exposure to microgravity and isolation [27].…”
Section: Electroencephalogram (Eeg)mentioning
confidence: 87%